Effects of Fibre Loading and Additives on the Properties of Rubberwood-Polypropylene Composites - Mohd Yunus, Nor Yuziah (2004)
The three parts study utilised rubberwood, polypropylene and additives in which rubberwood and polypropylene was melt blended, compressed and moulded prior to preparation of test samples. Samples were tested using ASTM standards, except for water absorption where British Standard was adopted. Spectroscopic analyses of Fourier Transform Infra-red spectroscopy (FTIR), Dynamic Mechanical Analysis (DMA) and Scanning Electron Microscopy (SEM) were carried out on the RWPC.